Modality analysis in Joe Biden’s speech delivered on the anniversary of the Covid-19 shutdown - Inggita Pramesti Ayuningtyas (Universitas Merdeka Malang, 2021)
Covid-19 has been global health problem and become the concern of global leaders in the world. One of them is Joe Biden, current president of American. He delivered his speech on Anniversary Covid-19 Shutdown on March 11, 2021. The clauses in his speech contain modality. Modality is included in interpersonal meaning where language is used to encode interaction between the speaker and the hearer. This research aims to analyze the type of modality used by Biden in his speech and utilize it to find his self-representation. The research uses Systemic Functional Grammar (SFG) in term of modality analysis as the tool and discourse analysis as the approach. The finding shows that three types of modalities found; inclination, probability and obligation. The self-representation of Biden found are being visionary, being determined, showing sadness, being powerful, and showing respect. DOI: 10.26905/enjourme.v6i2.6531